Penyelenggaraan Program Bantuan Hukum Berbasis Keadilan oleh Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Kalimantan Tengah - Venifera, Anggi Febrina (FOCUS, 2025)
The implementation of legal aid aims to guarantee and fulfil the rights of Legal Aid Recipients to obtain access to justice. In order to facilitate the implementation of legal aid programmes by Accredited Legal Aid Providers, BPHN created a web-based online application, namely the Application (SIDBANKUM). The formulation of the problem raised by the author is how the implementation of justice-based legal aid programmes through the SIDBANKUM Application by the Regional Office of the Ministry of Law and Human Rights of Central Kalimantan and how the obstacles and solutions in the implementation of justice-based legal aid programmes through the SIDBANKUM Application. The purpose of this research is to understand and explain the implementation of justice-based Legal Aid programmes through the SIDBANKUM Application by the Regional Office of the Ministry of Law and Human Rights of Central Kalimantan. This research uses an empirical juridical approach method. Primary data sources are obtained from the field and secondary data from documentation and legislation. The data collection technique is in the form of interviews with relevant agencies, namely the Regional Office of the Ministry of Law and Human Rights of Central Kalimantan. Then the research data is analysed descriptively qualitative. Based on the results of the research, the Regional Office of the Ministry of Law and Human Rights of Central Kalimantan has organised a Legal Aid Programme by referring to the Legislation and Legal Aid Service Standards. However, not everything went well due to, among others, the limited number of accredited legal aid providers, the lack of understanding of legal aid providers in using the Sidbankum application for the legal aid budget reimbursement process, and the lack of Non Litigation agenda Accredited legal aid providers related to disseminating information about the implementation of legal aid programmes. Through these obstacles, the Regional Office determined the solution steps, among others, such as by increasing the dissemination of information related to the implementation of the Legal Aid program, and optimising the use of the Sidbankum application for Legal Aid Providers, through Socialisation, Dissemination, FGDs, and the use of print and social media, as well as optimising monitoring and evaluation of Legal Aid Providers to always apply the Legal Aid Service Standards and Operational Standards for Providing Legal Aid Services.